2006
DOI: 10.1111/j.1440-1746.2006.04774.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening colonoscopy in asymptomatic average‐risk Koreans: Analysis in relation to age and sex

Abstract: Colonoscopy is a useful modality for colorectal cancer screening in Korea, as established in Western countries. However, the screening colonoscopy may begin at an older age for Koreans than for Westerners. Similarly, the optimal starting age for screening in Korean women may be higher than that in men by 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
35
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 23 publications
(62 reference statements)
5
35
6
Order By: Relevance
“…In comparison with other studies, our results are lower than previous reports from developed countries among the asymptomatic average-risk subjects (Lieberman et al, 2000;Choe et al, 2007;Rundle et al, 2008;Siegel et al, 2012;Ng and Wong 2013;Yang et al, 2014). Heitman et al reported in their meta-analysis that the prevalence of non-advanced, advanced adenoma and cancer in North America were 17.7%, 5.7% and 0.3%, respectively (Heitman et al, 2009).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…In comparison with other studies, our results are lower than previous reports from developed countries among the asymptomatic average-risk subjects (Lieberman et al, 2000;Choe et al, 2007;Rundle et al, 2008;Siegel et al, 2012;Ng and Wong 2013;Yang et al, 2014). Heitman et al reported in their meta-analysis that the prevalence of non-advanced, advanced adenoma and cancer in North America were 17.7%, 5.7% and 0.3%, respectively (Heitman et al, 2009).…”
Section: Discussioncontrasting
confidence: 55%
“…Researchers from Asian-pacific developed countries have also reported a significant increase of CRC over the last decades. It seems that these countries actually have the same incidence as western countries; this could be due to the "westernization" of lifestyles in these countries (Choe et al, 2007;Chung et al, 2010;Aswakul et al, 2012;Ng and Wong 2013;Yang et al, 2014). This discrepancy between our findings and theirs might be related to lifestyle, diet, younger population and also genetic differences.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Because cancer incidence tends to increase with age and CRC is more prevalent in males [20], the high incidence of CRC in elderly patients and males was not surprising. According to previous studies, male sex [6,21], age C50 years old [21], and smoking [6] were significantly associated with colorectal neoplasm (colorectal adenoma and cancer).…”
Section: Discussionmentioning
confidence: 99%